2017
DOI: 10.2807/1560-7917.es.2017.22.30.30579
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus seroprevalence and prevalence of chronic infection in the adult population in Ireland: a study of residual sera, April 2014 to February 2016

Abstract: Robust data on hepatitis C virus (HCV) population prevalence are essential to inform national HCV services. In 2016, we undertook a survey to estimate HCV prevalence among the adult population in Ireland. We used anonymised residual sera available at the National Virus Reference Laboratory. We selected a random sample comprising persons ≥ 18 years with probability proportional to the general population age-sex distribution. Anti-HCV and HCV Ag were determined using the Architect anti-HCV and HCV Ag assays. Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Our clearance rate of 45%, although based on a small number of positive samples, is higher than has been described by Seeff [19]. A similar clearance was observed by Garvey et al in Ireland [20]. Unfortunately, we do not have details on treatment history of the participants, nor on the number of treated individuals in Belgium, but most likely some of these individuals were known HCV positive and have received treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Our clearance rate of 45%, although based on a small number of positive samples, is higher than has been described by Seeff [19]. A similar clearance was observed by Garvey et al in Ireland [20]. Unfortunately, we do not have details on treatment history of the participants, nor on the number of treated individuals in Belgium, but most likely some of these individuals were known HCV positive and have received treatment.…”
Section: Discussionsupporting
confidence: 56%
“…A recent systematic review found that 13 EU/EEA countries had conducted HCV prevalence surveys with an estimated antiHCV prevalence in the EU/EEA of 1.1% (95% CI 0.9–1.4%) of which an estimated 70% have CHC [ 27 ]. In the Netherlands, a CHC prevalence of 0.16% was found using the workbook method, whereas Ireland and Belgium reported 0.98% and 0.13% CHC prevalence using residual sera testing [ 28 30 ]. However, none of these methods were directly comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review found that Ireland has low rates of HCV infection in the general population compared to other European countries [ 5 , 27 , 86 , 87 ]. The most up to data (residual sera study) showed a reduced prevalence compared to a 2012 mathematical modelling study [ 6 , 9 ]. The different rates could be explained by the differing methodologies or by a reduction in new infections.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries iatrogenic transmission of HCV has been substantially reduced and people who inject drugs (PWID) or have done so in the past are now the main group affected [ 1 – 5 ]. Of the 600,000 HCV infected people living in Europe an estimated 20,000–30,000 reside in Ireland [ 6 9 ]. An estimated 60% of HCV infections in Ireland remain undiagnosed [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation